2009
DOI: 10.1007/bf03245851
|View full text |Cite
|
Sign up to set email alerts
|

P2O5/SiO2 as an efficient and recyclable catalyst for N-Acylation of sulfonamides under heterogeneous and solvent-free conditions

Abstract: A convenient synthetic method for N-acylation of sulfonamides in the presence of P 2 O 5 /SiO 2 is described. Carboxylic acid anhydrides and carboxylic acid chlorides were used as acylating agents and the reactions were carried out in CH 2 Cl 2 or solventfree conditions. The catalyst can be recovered by simple filtration and can be used in the subsequent reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…On the other hand, solid supported reagents are unique catalysts that have become popular recently [38][39][40][41]. The high catalytic activity, low toxicity, moisture and air tolerance, recyclability, and particularly their low price make the use of solid supported reagents an attractive alternative to conventional acids.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, solid supported reagents are unique catalysts that have become popular recently [38][39][40][41]. The high catalytic activity, low toxicity, moisture and air tolerance, recyclability, and particularly their low price make the use of solid supported reagents an attractive alternative to conventional acids.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous research in organic synthesis, herein we reported the molecular docking, synthesis, and antibacterial activities of some novel sulfonamide‐amide derivatives under mild conditions (Scheme ). To the best of our knowledge, this is the first report on the synthesis of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our research on the acylation reactions [20][21][22][23], we wish to report here the synthesis of a series of new acylating reagents, which are useful for the chemoselective acylation of amino groups of compounds that possess both amino and other groups in water.…”
Section: Introductionmentioning
confidence: 99%